Uji Antagonis Trichoderma spp. Terhadap Phytophthora palmivora Butl. Penyebab Penyakit Busuk Buah Kakao (Theobroma cacao L.) - Riza Linda, Denisa Cikita, Siti Khotimah (Universitas Tanjungpura, 2016)
Cocoa (Theobroma cacao L.) is one of the plantation crops and major export commodity in Indonesia, but its development is widely still face barriers that their pests and diseases. Rotten fruit is the most dominant disease because it causes a large loss, one of the causes fruit rot disease is a fungal pathogen attack named Phytophthora palmivora (Butl.). This research aims to examine the ability of the fungus Trichoderma spp. insuppressing the growth of P. palmivora. Isolation and identification of fungi were calculated using direct planting method and dilution method, also the antagonists were tested in vitro. The results showed that three types of fungus Trichoderma found on cocoa plantations that Trichoderma sp. 1, Trichoderma harzianum, and Trichoderma viride. Based on the research results, T. viride most capable of inhibiting the growth of the fungus P. palmivora antagonist with highest percentage of 71.95%.